Urban environmental noise pollution and perceived health effects in Ibadan, Nigeria (2012)
Urban environmental noise pollution has impact on the quality of life and it is a serious health and social problem. The aim of this study was to assess the sources and noise levels, and possible impacts in selected residential neighbourhoods of Ibadan metropolis. Structured questionnaire was used to elicit information from respondents on demographic and neighbourhood characteristics, sources of noise and perceived effects of noise pollution. Noise level meter was used to determine the noise levels. Results showed that noise levels, sources and the period the noise level reaches its peak vary with population density and are shown on GIS maps. The mean noise values for the three residential neighbourhood groups were low density (LD), 53.10±2.80dB; medium density (MD), 68.45± 2.10dB and high density (HD), 68.36±1.92dB with the medium density neighbourhoods having the highest mean value. There is a significant difference in the noise levels in the three neighbourhood groups (F value=11.88 and p=0.000). However, the difference in noise levels between HD/LD and LD/MD areas was significant (p=0.000) while that between HD/MD areas was not significant (p=0.975). Of the three residential neighbourhoods, the highest mean noise level (85.80dB) was recorded at Bere junction while the lowest was at the foot of Bowers tower at Oke Are (48.65dB). Based on WHO 16-hour DNL criteria of 55dB for residential areas, only 16 (23.2%) locations in the three residential neighbourhood groups had noise values that were within the recommended limit. The study concludes that there is a need for formulation and enforcement of permissible noise levels/standards for residential neighbourhoods by the Federal Ministry of Environment instead of using the current eight-hour standard of 90dB which is for industrial settings.